Guide to medicinal plants of Trinidad and Tobago - Seaforth, C.E. (Commonwealth Secretariat LondonGB, 1983)
Describes and illustrates over one hundred plants still used for medicinal purposes in Trinidad and Tobage. For each specis gives physical description, habitat and distribution, description of its use in medicinal preparations, and its pertinent biodynamic data. Wherever applicable makes comparison with Wong's (1976) published findings about the use of the plant.